Histopathological studies on the synovial membrane of donkey with induced chronic arthritis following ultrasound therapy and antiarthritic drug treatment - Labana, Amar Iqbal Singh; Sobti, V K; Khan, Massarat; Saigal, R P (The Indian Journal of Animal Sciences, 2012)
The chronic arthritis was induced in the left intercarpal joint of 12 clinically healthy donkeys, 5-7years old, to assess the efficacy of ultrasound therapy and antiarthritic drug treatment. They were divided into groups A, B and C of 4 animals each. Groups B and C were further treated with antiarthritic herbal drug (ART) and ultrasound therapy (UST), respectively. The tissue samples of the synovial membranes were subjected to histological examination. The synovial membrane of group A animals having induced chronic arthritis with no treatment showed loss of synoviocytes, and fibrosis of subintima aud the joint capsule. The treatment with ART in group B evidenced the intimal proliferation and subintimal regenerative changes leading to nearly normal synovial membrane. In group C following the UST @ 1.5 w/cmÂ², the intimal proliferations and the mesenchymal tissue were localised but patches of degenerative changes were present. It was concluded that chronic arthritis responds to both the ART and UST treatments, but the former showed better regenerative changes